Adapting RGT solver interface to management strategy search problems - Tadevos S. Baghdasaryan (Изд-во НАН РА)
We develop a unified Solver for the class of problems where the space of possible solutions can be specified by reproducible game trees (RGT) [11]. In this paper we adapt the interface of RGT Solver for marketing and supply chain management (SCM) problems of the class presented by ValueWar and Trading Agents Competition models [1, 2, 4]. Particularly, we describe: - the ways for construction of operating entities, actions and strategy plans for the ValueWar tool,- the ways for construction of operating entities, actions, moves and strategy plans for the TAC SCM game.
Keywords: Mathematics; Computer software